2018
DOI: 10.1038/s41598-018-31013-4
|View full text |Cite
|
Sign up to set email alerts
|

Circulating H3Cit is elevated in a human model of endotoxemia and can be detected bound to microvesicles

Abstract: Early diagnosis of sepsis is crucial since prompt interventions decrease mortality. Citrullinated histone H3 (H3Cit), released from neutrophil extracellular traps (NETs) upon binding of platelets to neutrophils following endotoxin stimulation, has recently been proposed a promising blood biomarker in sepsis. Moreover, microvesicles (MVs), which are released during cell activation and apoptosis and carry a variety of proteins from their parental cells, have also been shown to be elevated in sepsis. In a randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 48 publications
1
22
0
3
Order By: Relevance
“…Previous studies in the non-cancer setting have indicated an association of NETs with arterial thrombosis (de Boer et al, 2013;Borissoff et al, 2013;Mangold et al, 2015;Perez-de-Puig et al, 2015;Riegger et al, 2016). However, most studies investigated NETs at the site of thrombus formation (de Boer et al, 2013;Mangold et al, 2015;Perez-de-Puig et al, 2015;Riegger et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies in the non-cancer setting have indicated an association of NETs with arterial thrombosis (de Boer et al, 2013;Borissoff et al, 2013;Mangold et al, 2015;Perez-de-Puig et al, 2015;Riegger et al, 2016). However, most studies investigated NETs at the site of thrombus formation (de Boer et al, 2013;Mangold et al, 2015;Perez-de-Puig et al, 2015;Riegger et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies in the non-cancer setting have indicated an association of NETs with arterial thrombosis (de Boer et al, 2013;Borissoff et al, 2013;Mangold et al, 2015;Perez-de-Puig et al, 2015;Riegger et al, 2016). However, most studies investigated NETs at the site of thrombus formation (de Boer et al, 2013;Mangold et al, 2015;Perez-de-Puig et al, 2015;Riegger et al, 2016). One study that evaluated circulating doublestranded DNA (dsDNA), nucleosomes, citrullinated Histone 4 (H4Cit) and myeloperoxidase-DNA complexes (MPO-DNA complexes) as NET formation markers found that baseline levels of dsDNA, nucleosomes and MPO-DNA are associated with the occurrence of major arterial cardiovascular events (Borissoff et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies from other investigators have unveiled CitH3 as potential diagnostic and prognostic blood marker associated with an exacerbated inflammatory response in patients with advanced cancer [ 20 ] and elevated in serval diseases like pneumonia, sepsis, and experimental endotoxemia [ 21 23 ]. Recently, Zuo et.al found that serum levels of CitH3 were increased in coronavirus disease 2019 (COVID-19) patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herein we report that in mice with either phenotype, of high (Wilson disease) and low (Menkes disease) copper levels in the liver, NET formation during endotoxemia was impaired whereas NET release during this condition is one of the hallmarks of the human reaction to LPS and has been proposed to serve as its promising blood biomarker (6,52). The fact that less NETs were formed in inflamed livers of Menkes mice correlates with hardly occurring neutrophil infiltration and impaired neutropoiesis is most probably directly responsible for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%